Ada Lovelace born in London. - Cavendish, Richard (History Today, 2015)
The article presents a brief profile of Ada Lovelace, the first computer programmer. Emphasis is given to topics such as her relationship with her father and poet Lord Byron, her education in science and mathematics, and her work with mathematician Charles Babbage including the sequencing of Bernoulli numbers.